2020
DOI: 10.1002/esp.4916
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of a time‐varying wave angle on the nonlinear evolution of sand bars in the surf zone

Abstract: Sandy beaches are often characterized by the presence of sand bars, whose characteristics (growth, migration speed, etc.) strongly depend on offshore wave conditions, such as wave height and angle of wave incidence. This study addresses the impact of a sinusoidally time‐varying wave angle of incidence with different time‐means on the saturation height, migration speed and longshore spacing of sand bars. Model results show that shore‐transverse sand bars (so‐called TBR bars) eventually develop under a time‐vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…These results are similar to those of Nnafie et al. (2020) in the case of one single shore‐parallel bar. This halving of the response period can be explained based on Figure 14.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results are similar to those of Nnafie et al. (2020) in the case of one single shore‐parallel bar. This halving of the response period can be explained based on Figure 14.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of single‐barred beach system, Nnafie et al. (2020) constructed a similar curve as the ones showed in Figure 14 and found that the mean bar height in the cases of a time‐varying wave is the same as that in the case of a time‐invariant angle when T ≪ T a . In the present study, bars in the inner domain initially do have the same mean height as those of a time‐invariant angle (result not shown).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations